Effects of whale-watching activities on southern right whales in Encounter Bay, South Australia. (April 2023) - Sprogis, Kate R.; Holman, Dirk; Arranz, Patricia; Christiansen, Fredrik
Abstract: Southern right whales ( Eubalaena australis ) are listed as Endangered under the Australian EPBC Act 1999. They migrate to shallow, coastal waters during the winter to mate, calve and nurse their young. During this time, they are easily accessible to the boat-based whale-watching industry. The aim of the study was to determine if whale-watching at 300 m distance affects the behaviour of southern right whales. To achieve this, behavioural focal follows on mother-calf pairs were conducted using unmanned aerial vehicles (UAVs) in the presence and absence of a commercial whale-watching vessel. There was no significant effect of phase ( control, before, during, after ) on the whales' respiration rate, swim speed, nursing rate and duration, maternal rate of active behaviours, tactile contact or calf pectoral fin contact. There was a significant reduction in resting between control and after phases, for both mothers (from 62% to 30%) and calves (from 16% to 1%). At 300 m distance and slow speed, vessel noise was measured to be slightly above ambient noise at the lower TOL0.25 kHz band, however, vessel noise was masked by ambient noise within the higher frequency TOL2–10 kHz bands. A factor which may have contributed to a decline in resting after whale-watch approaches, was an increase in vessel speed upon departure, which consequently increased vessel noise. Based on this, we recommend that vessels maintain a slow speed ( e.g., ≤10 knots) within 1 km distance from the whales whilst conducting whale-watch activities. Highlights: There was no effect of whale-watching on respiration rate, swim speed or nursing. Resting for mothers halved after whale-watching compared to control data. Resting for calves declined to near null after whale-watching compared to control. Fast departure speeds after encounters appear to disturb resting behaviour. We recommend that vessels maintain slow speed within 1 km to whales.